Evidence for a Causal Role of the SH2B3-β2M Axis in Blood Pressure Regulation: Framingham Heart Study. Issue 2 (February 2019) - Keefe, Joshua A.; Hwang, Shih-Jen; Huan, Tianxiao; Mendelson, Michael; Yao, Chen; Courchesne, Paul; Saleh, Mohamed A.; Madhur, Meena S.; Levy, Daniel
Abstract : Genetic variants at SH2B3 are associated with blood pressure and circulating β2 M (β-2 microglobulin), a well-characterized kidney filtration biomarker. We hypothesize that circulating β2 M is an independent risk predictor of hypertension and may causally contribute to its development. The study sample consisted of 7 065 Framingham Heart Study participants with measurements of plasma β2 M. Generalized estimating equations were used to test the association of β2 M with prevalent and new-onset hypertension. There were 2 145 (30%) cases of prevalent hypertension at baseline and 886 (21%) cases of incident hypertension during 6 years of follow-up. A 1-SD increase in baseline plasma β2 M was associated with a greater risk of prevalent (odds ratio 1.14, 95% CI 1.05–1.24) and new-onset (odds ratio 1.18, 95% CI 1.07–1.32) hypertension. Individuals within the top β2 M quartile had a greater risk than the bottom quartile for prevalent (odds ratio 1.29, 95% CI 1.05−1.57) and new-onset (odds ratio 1.59, 95% CI 1.20–2.11) hypertension. These associations remained essentially unchanged in analyses restricted to participants free of albuminuria and chronic kidney disease. Mendelian randomization demonstrated that lower SH2B3 expression is causal for increased circulating β2 M levels, and in a hypertensive mouse model, knockout of Sh2b3 increased β 2 M gene expression. In a community-based study of healthy individuals, higher plasma β2 M levels are associated with increased risk of prevalent and incident hypertension independent of chronic kidney disease status. Overlapping genetic signals for hypertension and β2 M, in conjunction with mouse knockout experiments, suggest that the SH2B3 -β2 M axis plays a causal role in hypertension. Abstract : Supplemental Digital Content is available in the text.